Changes to Articulatory Kinematics in Response to Loudness Cues in Individuals with Parkinson’s Disease - Darling, Meghan (2011)
PURPOSE: Individuals with Parkinson’s disease (PD) exhibit differences in displacement and velocity of the articulators as compared to older adults. The purpose of the current study was to examine effects of three loudness cues on articulatory movement patterns in individuals with PD. METHODS: Nine individuals diagnosed with idiopathic PD and 9 age- and sex- matched healthy controls produced sentences in four conditions: 1) comfortable loudness, 2) targeting 10dB above comfortable, 3) twice as loud as comfortable, and 4) in background noise. Lip and jaw kinematics and acoustic measurements were obtained. RESULTS: Both groups significantly increased sound pressure level (SPL) in the loud conditions as compared to comfortable. For the loud conditions, both groups had the highest SPL in background noise and 10dB and the lowest in twice as loud. Control participants produced the largest opening displacement in background noise and the smallest in twice as loud. Conversely, individuals with PD produced the largest opening displacement in twice as loud and the smallest in background noise. CONCLUSIONS: Control participants and individuals with PD responded to cues to increase loudness in different ways. Changes in SPL may explain differences in kinematics for the control participants, but do not for individuals with PD.